Contamination of rare earth elements in coastal seawaters from nearby industrial complexes, Korea - Seong-Hu Choi; Man Sik Choi; Dong-Jin Joe; Da-Som Yang; Min-Jae Lee; Seung-Gyu Park (Marine Pollution Bulletin, 2026)

Particulate matter 2.5 promotes HIF-1α-associated autophagy and epithelial–mesenchymal transition in 3D retinal pigment epithelial spheroids - Da Hye Kim; EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Hyesook Lee; Su Hyun Hong; Gi Young Kim; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2026)

Integration of PMF and metal isotopes for source tracking in the metal contaminated sediments of a semi-enclosed estuary (Pohang Old Port, South Korea) - Dong-Jin Joe; Man Sik Choi; Seok-Yoon Jang; Youn-Joong Jeong; Da-Som Yang; Min-Jae Lee (Marine Pollution Bulletin, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

K2FeO4-modified vinasse biochar reduces chromium accumulation in rice grains and enhances Cr(VI) reduction in paddy soil - Min Xu; Yinchen Da; Yutao Gao; Jun Wu; Chao Chen; Lulu Long; Min Deng; Bo Zhang; Gang Yang; Jing Ma (Environmental Science and Pollution Research, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

In Vivo micronucleus assay: Increased efficiency with an automated imaging system - Seng-Min Back; Da Yeon Kim; Ho Bin Yi; Na-Young Jeung; Nan-Young Kim; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Benzophenone-type UV filters in aquatic ecosystems: Sources, toxicological impacts, and interactions with coexisting stressors - Yu Ri Jin; Mi-Song Hong; Jin-Sol Lee; Jiezhang Mo; Piotr Maszczyk; Menghong Hu; Youji Wang; Zhou Yang; Minghua Wang; Da-Zhi Wang; Min-Chul Lee; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Non-Cytopathic Mammalian Orthoreovirus Infection Triggers Innate Immune Responses in Human Tonsil-Derived Mesenchymal Stem Cells: Implications for Cell Therapy Quality Control - Jeong Eun Kim; Ji Yeong Noh; Kyeong Eun Lee; Young Il Lee; Juyun Park; Min Chan Kim; Da Hyeon Choi; Hye Ji Jung; Hee Sung Jung; Jung Won Park; Eun-Ok Lee; Van Thi Lo; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Techno-economic assessment of bioenergy with carbon capture and storage for Brazilian thermoelectric power plants - Fazal Um Min Allah; Rodrigo Nogueira De Sousa; Elena Trim; Adriano da Silva Marques; Monica Carvalho (Biomass and Bioenergy, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Investigating the mechanisms of motion response amplification for a cylindrical FPSO under wave-current coupling - Min Li; Da Li; Shenglei Fu; Yuan Zhuang; Decheng Wan (Ocean Engineering, 2026)

New grylloblattid insect from the Lower Triassic Kayitou Formation of Yunnan Province, Southwest China - Shi-Xue Hu; Jin-Yuan Huang; Qi-Yue Zhang; Chang-Yong Zhou; Wen Wen; Xiao Min; Da-Ran Zheng; Qian-Qi Zhang (Palaeoworld, 2026)

Enhanced chlorine photolysis and 1H-benzotriazole degradation in water under the Far-UVC (UV222) irradiation - Jia-Jing Lyu; Qing Bai; Qian-Yuan Wu; Yu-Jia Nong; Mu-Da Han; Min-Yong Lee; Zhong-Quan Ren; Jiang-Lei Xiong; Wen-Long Wang (Journal of Environmental Chemical Engineering, 2026)

Elucidation of caffeine degradation in kombucha by Komagataeibacter saccharivorans KS1 and low-caffeine kombucha production - Da-Eun Jang; Seong-Jin Hong; Ki-Nam Yoon; Hye-Jin Kang; Ok Cheol Kim; Young-Min Kim (Food Bioscience, 2026)

Tailor-made sulfonated lignin derivatives with controllable anionic charge and enhanced aqueous solubility for the fabrication of uniform microspheres - Ji Won Heo; Min Soo Kim; Min Sun Kwon; Da Ye Kim; Ji Won Yang; Yong Sik Kim (Chemical Engineering Journal, 2026)

Heavy metal contamination and sources thereof in Oehwang River estuarine sediments from Ulsan Bay, Korea, based on heavy metals and lead isotope ratios - Da-som Yang; Man-sik Choi; Dong-jin Joe; Min-jae Lee (Environmental Monitoring and Assessment, 2026)

Tm4sf19 inhibition alleviates imiquimod-induced psoriatic dermatitis by regulating inflammatory signaling pathways and keratinocyte proliferation in mice - Min Gi Kang; Sujin Park; Eunji Hong; Min-Jung Lee; Da Seul Jung; Jin Sun Heo; Haein An; Min Woo Kim; Naim Park; Hyeyeon Park; Pyunggang Kim; Minjung Son; et al. (Inflammation Research, 2026)

Quantifying soil micro-element state distribution and predicting tillage performance during sodic saline-alkali subsoiling based on mathematical model and DEM simulation approach - Min Liu; Jinchun Sun; Pinyan Lv; Dongyan Huang; Da Qiao; Yingjie Guo; Weizhi Feng; Daping Fu; Limin Jiang; Jingli Wang (Computers and Electronics in Agriculture, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

A Randomized, Double-Blind, Placebo-Controlled Study on Probiotic Treatment for Halitosis: Novel Insights into Glucose and Phosphorus Metabolism - Ji Hye Choi; Sehyeon Song; Min Ji Jang; Md Ariful Haque; Hye Eun Lee; Da Hui Kim; Yeo Ju Kim; Ja Won Cho; Jin Seok Moon; Keon Heo; Myeong Soo Park; Seockmo Ku (Probiotics and Antimicrobial Proteins, 2026)
Halitosis, or bad breath, is associated with oral microbial imbalances and the production of volatile sulfur compounds (VSCs). While existing treatments target pathogenic bacteria or oral health indicators, they may not address the underlying systemic complexity. This study explored the efficacy of Complex OK oral probiotics containing Lactobacillus gasseri HHuMIN D and L. paracasei OK in mitigating halitosis by evaluating VSC levels and metabolic markers. A 12-week, randomized, double-blind, placebo-controlled clinical trial was conducted involving 80 participants, 70 of whom completed the study in South Korea (KCT0009894). The participants were selected based on the presence of 2 of 3 pathogenic oral bacteria ( F. nucleatum , P. gingivalis , and P. intermedia ) and baseline VSCs > 2.0 ng/10 mL. Exclusion criteria included systemic diseases, recent antibiotic/probiotic use, and severe dental conditions. Oral health, VSCs, and metabolic markers were assessed using paired t -tests, ANCOVA, and Wilcoxon rank-sum tests. Despite unchanged oral health indicators and levels of harmful bacteria, probiotic supplementation showed efficacy in maintaining microbial balance. Significant reductions in H₂S and total VSCs were observed in the experimental group compared to the placebo ( P < 0.05). No significant changes were observed in oral health indices or levels of harmful oral bacteria, but the experimental group showed a significant decrease in blood glucose ( P = 0.009) and an increase in phosphorus levels ( P < 0.05). This study provides the first published evidence linking systemic metabolic regulation to halitosis reduction, suggesting that probiotics mitigate bad breath through glucose and phosphorus metabolism rather than by direct bacterial inhibition. Further research is needed to confirm these findings and to explore the underlying mechanisms.

Co-infection of feline coronavirus with feline parvovirus alters plaque phenotypes and single-nucleotide-variant frequencies compared with single infection in CRFK cells - Ha Yeon Kim; Van Thi Lo; Seong Sik Jang; Min Chan Kim; Alain Chrysler Chamfort; Da Young Mun; Min Chang Kang; Han Byul Lee; Dae Gwin Jeong; Hyoung Joon Moon; Hye Kwon Kim (Toxicology and Environmental Health Sciences, 2026)

Assessment of space weather modeling capabilities and transition to operations - Maria M. Kuznetsova; Martin A. Reiss; Edmund Henley; Eric Adamson; Suzy Bingham; Mario M. Bisi; François-Xavier Bocquet; Laura Boucheron; Min-Yang Chou; Claudio Corti; Gian Luca Delzanno; Richard A. Fallows; et al. (Advances in Space Research, 2026)

Polydeoxyribonucleotides isolated from the food fermentation strain Enterococcus faecium mitigate neuroinflammation via MAPK-mediated BMP/SMAD/Wnt regulation under neuro-oxidative stress - Da Hye Song; Yu-Rim Lee; Seung Min Yu; Soo Youn Lee; Sae-Hun Kim; Jeung Hee An (Food Bioscience, 2026)

Hematology-centered homeostatic immunity confers durable resistance to rock bream iridovirus (RBIV) in rock bream (Oplegnathus fasciatus) - Su-Mi Shin; Min-Sung Kim; Da-Seul Lee; Dong-Jin Lim; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

Spatiotemporal variability in the biochemical characteristics of phytoplankton and zooplankton in the coastal waters of the Yellow and East seas - Da Won Goh; Min Ho Seo; Young Seok Jeong; Jun Sik Woo; Sanghoon Park; JaeSoon Kim; Myung Joon Kim; Yoon Ji Lee; Ye Hwi Kim; Ha Young Choi; Hye Min Choi; Sang Heon Lee (Estuarine, Coastal and Shelf Science, 2026)

Catalytic conversion of fatty acid methyl esters to biofuels under mild reaction conditions - Xiaolong Yan; Lei Wang; Weimin Da; Yawen Shi; Zhaowei Tian; Zhitong Qian; Yu Sun; Xu Zhao; Xin Zhang; Weiming Zhai; Feng Liu; Yusen Yang; et al. (Chemical Engineering Journal, 2026)

Early warning strategy of thermal runaway for aviation lithium-ion batteries from operando parameters evaluation - Juan Yang; Yu Yang; Wei Deng; Tiantian Liu; Da Chen; Min Wang; Jiang Xie; Qingsong Zhang (Chemical Engineering Journal, 2026)

Effective production of biosyngas from biomethane over spatially confined Ni catalyst with captured CO2 - Su-Ji Kim; Yeon Jeong Yu; Sung-Bin Choi; Gwan-Joong Park; Da-Bin Kang; Byung Sun Yoon; Ye-Eun Jeon; Min-Young Kim; Jeong-Chul Kim; Young-Kwon Park; Chang Hyun Ko (Bioresource Technology, 2026)

Plant-derived CD200-Fc promotes tight junction integrity in bladder epithelial cells - Da Won Lee; Jeong Hwan Lee; Chae Eun Lee; Jong Seok Lim; Sohee Lim; Jin Wook Kim; Soon Auck Hong; Min Eui Hong; Joo Young Kim; Hye Jun Lee; Kisung Ko; Soon Chul Myung (Plant Biotechnology Reports, 2026)

Distinguishing three flounder species in the East Sea of Korea using otolith and body morphometric analysis - Samroz Majeed; Min Gu Kang; Nurfakhira Lani; Haryun Kim; Hyun Soo Rho; Maeng Jin Kim; Laith A. Jawad; Da Yeon Kang; Joo Myun Park (Regional Studies in Marine Science, 2026)

A mixed copula–KDE framework for joint modeling of streamflow and sediment diversion - Chao Tan; Xi Yang; Zhifa Luo; Da Liu; Fenghua Huang; Min Qin (Stochastic Environmental Research and Risk Assessment, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Key factors regulating springtime phytoplankton primary production in the coastal waters of South Korea - Hye Min Choi; Kwanwoo Kim; Hyo Keun Jang; Jun Sik Woo; Yejin Kim; Sanghoon Park; Jaesoon Kim; Myung Joon Kim; Yoon Ji Lee; Ye Hwi Kim; Hayoung Choi; Da Won Goh; et al. (Regional Studies in Marine Science, 2025)

Chemo-biostratigraphy of the Dzabkhan Craton: Refining the Ediacaran-Cambrian Transition in Southwestern Mongolia - Xiao Tang; Da Li; Simon V. Hohl; Michael Steiner; Ben Yang; Yi-Sheng Yin; Zhong-Lai Zhou; Qiao Li; Min Wu (Global and Planetary Change, 2025)

Migration of organic and inorganic antimicrobials from antimicrobial-labeled food packaging and probabilistic risk assessment implications - Kyung Youn Lee; Hogeon Lee; Hee Seon Shin; Da Hee Ryu; Hyebin Yeo; Hae Min Ju; Dae Yong Jang; Ye Ji Koo; Seung Ha Lee; Kyung Min Lim; Dal Woong Choi (Food Packaging and Shelf Life, 2025)

Preparation and functional analysis of peripheral blood leukocytes in hybrid grouper (Epinephelus fuscoguttatus × E. lanceolatus) - Min-Da Yang; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Cadmium-induced nucleus pulposus derived mesenchymal stem cells apoptosis via MAPK signaling pathway contributes to IVD degeneration - Man Hu; Yu Zhang; Wen-jie Zhao; Xin Liu; Yan-feng Zhang; Da-xu Liu; Xin-min Feng; Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Bioconversion and characteristics of the rebaudioside D-like compound by glucosyltransferases combination - Hye-Jin Kim; Ok Cheol Kim; Seong-Jin Hong; Hye-Jin Kang; Da Eun Jang; Boo-Su Park; Jeong-Yong Cho; Young-Min Kim (Food Chemistry, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

The short-term and long-term effects of oil spill exposure on dyslipidemia: A prospective cohort study of Health Effects Research on the Hebei Spirit Oil Spill - Jiyoun Lee; Da-An Huh; Lita Kim; Kangyeon Park; Yun-Hee Choi; Se-Hyun Hwang; Woohyun Lim; Hyeon Jeong Choi; Kyong Whan Moon; Min-Sung Kang; Yong-Jin Lee (Marine Pollution Bulletin, 2025)

Dating of Early Triassic Chaohu Fauna by precise U-Pb age constraints: Temporal calibration of the emergence and first radiation of Mesozoic marine reptiles - Yi-Nuo Wang; Da-Yong Jiang; Ryosuke Motani; Ming-Tao Yao; Min Zhou; Zuo-Yu Sun; Jian-Dong Huang; Zhao-Liang Ma (Palaeoworld, 2025)

Effects of exogenous L-glutamic acid and supplemental LED lighting on the growth and yield of Paprika - Yong Beom Kwon; Joo Hwan Lee; Min Ji Kim; Da Young Lee; In-Lee Choi; Hyuk Sung Yoon; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Particulate matter 2.5 stimulates pyroptosis and necroptosis via the p38 MAPK/Akt/NF-κB signaling pathway in human corneal epithelial cells - Da Hye Kim; Hyesook Lee; Min Yeong Kim; Hyun Hwangbo; Seon Yeong Ji; EunJin Bang; Su Hyun Hong; Gi Young Kim; Sun-Hee Leem; Dongryeol Ryu; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2025)

Controlling high-concentration precursor crystallization to minimize photon loss in bifacial perovskite solar cells - Shan Gan; Haoxuan Sun; Min Wang; Da Dou; Siyang Zhang; Chen Li; Liang Li (Science Bulletin, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Fabrication and mechanism of microspheres with tunable and control-released hydrophobicity in a wide-range: Ultra-low-density proppant - Zhenyong Li; Yang Zhou; Da Zhang; Min Xu; Rui Li; Xianyan Ren (Fuel, 2025)

How does UVC-LED combined vacuum packaging impact pea protein-based patties? - Júlia Moraes da Costa Marques; Bruno Dutra da Silva; Ana Júlia Bento do Amaral; Gabriela Hsieh Min Yi; Luiz Torres Neto; Juliana Fidelis dos Santos Ferreira; Maria Lúcia Guerra Monteiro; Carlos Adam Conte-Junior (Food and Humanity, 2025)

Hollow-whisker modified calcium phosphate loaded with deferoxamine to promote osteoporotic bone regeneration by acting HIF-1α signaling pathway - Linyun Tan; Wacili Da; Cong Feng; Yitian Wang; Xin Hu; Guifeng Du; Hao Wang; Minghao Sun; Yuanrui Luo; Jingyang Li; Xiangfeng Li; Li Min; et al. (Chemical Engineering Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Corrigendum to “Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export” [Postharvest Biol. Technol. 219, January 2025, 113238] - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Chemical constituents of Himantormia lugubris collected from Antarctica and their PTP1B and α-glucosidase inhibitory activities - Manh Tuan Ha; Thi Thanh Le; Da Yeong Lee; Chung Sub Kim; Ui Joung Youn; Sang Hee Kim; Jeong Ah Kim; Byung Sun Min (Phytochemistry Letters, 2025)

Associations of polycyclic aromatic hydrocarbons exposure with serum uric acid and hyperuricemia in US adults: The role of systemic inflammation - Yang Liu; Xuejie Ding; Linling Yu; Da Shi; Ruyi Liang; Wei Liu; Xuezan Huang; Xiuyu Cao; Min Zhou; Weihong Chen (Journal of Environmental Sciences, 2025)

A formula of quantile of extreme wind pressure coefficient to estimate wind load with various mean recurrence intervals - Lin Da; Qingshan Yang; Min Liu; Ke Zhou; Chuang Li (Engineering Structures, 2025)

Far-red light-driven photoautotrophy of chlorophyll f-producing cyanobacterium without red-shifted phycobilisome core complex - Da Huang; Tong Wei; Min Chen; Shu-Jun Chen; Jia-Yue Wu; Lu-Dan Zhang; Hai-Feng Xu; Guo-Zheng Dai; Zhong-Chun Zhang; Bao-Sheng Qiu (Photosynthesis Research, 2025)

Expression and in vitro function of anti-CTLA-4 human antibody expressed in plants - Chae Eun Lee; Jeong Hwan Lee; Hyun Joo Chung; Sohee Lim; Da Won Lee; Jong Seok Lim; Jin Wook Kim; Soon Auck Hong; Min Eui Hong; Joo Young Kim; Hye Jun Lee; Kisung Ko; et al. (Plant Biotechnology Reports, 2025)
Biosimilars produced in plant systems encompass a range of molecules, including antibodies, vaccines, enzymes, receptors, and other therapeutic molecules. In the present study, we aimed to express the immune checkpoint-inhibitor anti-CTLA-4 antibody, Ipilimumab, in Nicotiana tabacum plant. We generated transgenic tobacco plants using Agrobacterium -mediated transformation and purified an anti-CTLA-4 monoclonal antibody (mAb P CTLA-4) using protein A affinity chromatography. This purified mAb P CTLA-4 showed specific binding activity to CTLA-4-positive human tonsil tissues, as confirmed by immunoblot, indirect ELISA, and immunohistochemistry analyses. Our study confirmed that mAb P CTLA-4 effectively targeted CTLA-4 in human tonsil tissues. These findings suggest that our plant-derived anti-CTLA-4 antibody retains its original functionality, underscoring the promising potential of plant-based therapeutic expression systems for producing high-value medicinal biosimilars.

Research on fault diagnosis method and interpretability of nuclear power plant based on hybrid transformer model - Gui Zhou; Min-jun Peng; Hang Wang; Da-bin Sun; Zi-kang Li (Annals of Nuclear Energy, 2025)

Immune-enhancing effects of enzymatic hydrolysates of peanut sprouts in RAW 264.7 macrophages and cyclophosphamide-induced immunosuppressed mouse model - Chi Heung Cho; Gahee Youm; Kyung Min Lim; Mingyeong Kim; Da Kyoung Lee; Yong Baik Cho; Heong-Jun Yu; Hee Soon Shin; Sang-Hoon Lee (Food Research International, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Metaproteomics reveals metabolic activities potentially involved in bloom formation and succession during a mixed dinoflagellate bloom of Prorocentrum obtusidens and Karenia mikimotoi - Hua-Min Cheng; Xiao-Lian Ning; Shu-Feng Zhang; Hao Zhang; Lin Lin; Si-Qi Liu; Da-Zhi Wang (Science of The Total Environment, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Extraction of antimicrobial peptides from pea protein hydrolysates by sulfonic acid functionalized biochar - Min Liu; Xian-Da Hu; Xiang-Yu Huang; Li Wen; Zhou Xu; Li Ding; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

A Comparative Proteomics Study Revealing the Impact of Growing Region and Cultivar on Protein Expression in the Leaves of Nicotiana tabacum Plants - Yongxu Hu; Min Chen; Gang Li; Da Wu; Xiangmin Zhang (Plant Molecular Biology Reporter, 2024)

Clinical impact of major pathogenic genotypes of Pseudomonas aeruginosa associated with refractory chronic suppurative otitis media - Chang Hyeon Lee; Kyu-Min Kim; Jeong-Ih Shin; Da Min Jeong; Jung-Hyun Byun; Myung Hwan Jung; Hyung-Lyun Kang; Kee Woong Kwon; Seung Chul Baik; Woo-Kon Lee; Seong-Ki Ahn; Chae Dong Yim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Understanding the fouling characteristics in ultrafiltration membrane for marine algae-laden seawater pretreatment: Focus on the role of algal extracellular organic matter - Weilong Yang; Feng Zhou; Jaewon Lee; Junghyun Kim; Da Yun Kwon; Youngjin Kim; Hongqiang Ren; Seungkwan Hong; Min Zhan; Bing Wu (Journal of Cleaner Production, 2024)

On CO2 efficiency and trade-offs between sustainability, safety, economy and resilience in infrastructure developments - Min Liu; Da-Gang Lu; Michael Havbro Faber (Sustainable Cities and Society, 2024)

Particle-ozone complex pollution under diverse synoptic weather patterns in the Yangtze River Delta region: Synergistic relationships and the effects of meteorology and chemical compositions - Yangzhihao Zhan; Min Xie; Bingliang Zhuang; Da Gao; Kuanguang Zhu; Hua Lu; Tijian Wang; Shu Li; Mengmeng Li; Yi Luo; Runqi Zhao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Investigation of the sustainable production of ethylene oxide by electrochemical conversion: Techno-economic assessment and CO2 emissions - Ji Eun Yoon; Ki Bong Lee; Chun-Jae Yoo; Byoung Koun Min; Dong Ki Lee; Da Hye Won; Sangwon Kim; Jong-Ho Moon; Changsoo Kim; Ung Lee (Journal of Cleaner Production, 2024)

Establishments of G3BP1-GFP stress granule monitoring system for real-time stress assessment in human neuroblastoma cells - Sangsoo Lee; Da-Min Jung; Eun-Mi Kim; Kee K. Kim (Chemosphere, 2024)

Two-year carcinogenicity study of a novel plasticizer, bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate (Eco-DEHCH), by oral diet in Han Wistar rats - Da Som Jeong; Ji-Young Lee; Hyo-Jeong Han; Soo Min Ko; Dong Hyun Lee; Yerin Lee; Woo-Chan Son (Regulatory Toxicology and Pharmacology, 2024)

Orchids acquire fungal carbon for seed germination: pathways and players - Da-Ke Zhao; Zong-Min Mou; Yong-Ling Ruan (Trends in Plant Science, 2024)

Cancer risk associated with low-dose ionizing radiation: A systematic review of epidemiological and biological evidence - Shu Min Tao; Le Le Wang; Min Da Li; Jing Wang; Hong Mei Gu; Long Jiang Zhang (Mutation Research - Reviews in Mutation Research, 2024)

Current status, challenges and future prospects of carbon capture and storage (CCS) for thermal power plants in Brazil - Fazal Um Min Allah; Adriano da Silva Marques; Monica Carvalho (International Journal of Greenhouse Gas Control, 2024)

Improvement of 1,3-propanediol production from glycerol using formate as an intermediary metabolite for NADH regeneration in Klebsiella oxytoca - Eun Joo Park; Minsoo Kim; Da Seul Kong; Eunseo Kim; Won Gyeong Park; Jungho Jae; Min Jang; Byong-Hun Jeon; Jung Rae Kim (Biomass and Bioenergy, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

A new G3BP1-GFP reporter system for assessing skin toxicity by real-time monitoring of stress granules in vitro - Eunhye Kwon; Da-Min Jung; Eun-Mi Kim; Kee K. Kim (Toxicology Letters, 2024)

A novel method for underactuated UUV tracking unknown contour based on forward-looking sonar - Zheping Yan; Xuyu Min; Da Xu; Dong Geng (Ocean Engineering, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Corrigendum to “Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface” [Ocean Eng. 297, April 2024] - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Optimizing utilization strategy of real-time SHM information for structural integrity management based on preposterior decision analysis - Wei-Heng Zhang; Jianjun Qin; Da-Gang Lu; Min Liu; Michael Havbro Faber (Ocean Engineering, 2024)

Thalassinoides ichnofabrics from the Zhangxia Formation (Cambiran Miaolingian series) in Henan province: Bioturbators as Ecosystem engineers - Bingchen Liu; Yong'an Qi; Min Wang; Wenyi He; Yaogang Du; Da Li; Mingyue Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Targeted Metabolomic Biomarkers for Stroke Subtyping - Eung-Joon Lee; Da Jung Kim; Dong-Wan Kang; Wookjin Yang; Han-Yeong Jeong; Jeong-Min Kim; Sang-Bae Ko; Seung-Hoon Lee; Byung-Woo Yoon; Joo-Youn Cho; Keun-Hwa Jung (Translational Stroke Research, 2024)

Multigenerational effects of elevated temperature on host-microbiota interactions in the marine water flea Diaphanosoma celebensis exposed to micro- and nanoplastics - Min-Sub Kim; Young Hwan Lee; Yoseop Lee; Haksoo Jeong; Minghua Wang; Da-Zhi Wang; Jae-Seong Lee (Journal of Hazardous Materials, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Association between oil spill clean-up work and thyroid cancer: Nine years of follow-up after the Hebei Spirit oil spill accident - Yun-Hee Choi; Lita Kim; Da-An Huh; Kyong Whan Moon; Min-Sung Kang; Yong-Jin Lee (Marine Pollution Bulletin, 2024)

Long-term effects of the Hebei Spirit oil spill on the prevalence and incidence of allergic disorders - Se Hyun Hwang; Yong-Jin Lee; Yun-Hee Choi; Da-An Huh; Min-Sung Kang; Kyong Whan Moon (Science of The Total Environment, 2024)

High-performance pulse light stable perovskite indoor photovoltaics - Chen Li; Haoxuan Sun; Min Wang; Shan Gan; Da Dou; Liang Li (Science Bulletin, 2024)

Encapsulation of probiotics with poly-γ-glutamic acid alters gut microbiota and short-chain fatty acid content by maintaining cell viability in the gastrointestinal tract - Won Je Jang; Dong Nyoung Oh; Da Yeong Kim; Eun Ji Lee; Jong Min Lee (Food Hydrocolloids, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

NiFe layered double hydroxides synthesized based on solvent properties as anode catalysts for enhanced oxygen evolution reaction - Yoonhi Gu; Deok-Hye Park; Min-Ha Kim; Jeong-Hyeon Byeon; Da-Mi Lim; Seon-Ha Park; Ji-Hwan Kim; Jae-Sung Jang; Kyung-Won Park (Chemical Engineering Journal, 2024)

Therapeutic effect of intraperitoneal dexamethasone on noise-induced permanent threshold shift in mice model - Byeonghyeon Lee; Min-Cheol Kim; Ye-Ri Kim; Jong-Heun Kim; Tae-Jun Kwon; Da Jung Jung; Un-Kyung Kim; Kyu-Yup Lee (Experimental Brain Research, 2024)

Study on the performance of Anerinibacillus sp. in degrading cyanide wastewater and its metabolic mechanism - Yao-ting Duan; Wei-da Wang; Si-yuan Qin; Xin Xu; Bo-xi Li; Min-jie Chen; Chun-li Zheng (Chemosphere, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Neurotrophic phenolic glycosides from the roots of Armoracia rusticana - Tae Hyun Lee; Da Hye Yoon; Kyoung Jin Park; Seong-Min Hong; Minji Kim; Sun Yeou Kim; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Exploring the antioxidant “cut-off effect” of gallic acid alkyl esters in dried oysters (Crassostrea gigas) during storage - Guan-Hua Zhao; Ying Luo; Qi Li; Min Zhang; Fa-Wen Yin; Da-Yong Zhou (Food Bioscience, 2023)

Changes in lake area and water level in response to hydroclimate variations in the source area of the Yellow River: a case study from Lake Ngoring - Yang Pu; Min Zhan; Xiaohua Shao; Josef P. Werne; Philip A. Meyers; Jiaojiao Yao; Da Zhi (Frontiers of Earth Science, 2023)

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

Photothermal effect-enhanced peroxidase-like performance for sensitive detection of organophosphorus pesticides on a visual test strip - Yiming Wang; Min Li; Zirui Wang; Jing Xu; Junjian Zhao; Zhi-Da Gao; Yan-Yan Song (Chemical Engineering Journal, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

Evidence for the circulation of genotype 4 Eurasian avian-like lineage swine H1N1 influenza A viruses on Korean swine farms, obtained using a newly developed one-step multiplex RT-qPCR assay - Soo Hyun Moon; Woonsung Na; Seongho Shin; Hyunil Kim; Ji Yeong Noh; Seong Sik Jang; Min Chan Kim; Hyun A. Lim; Ha Yeon Kim; Da Young Mun; Sun-Woo Yoon; Hye Kwon Kim (Archives of Virology, 2023)

Preparation of basic magnesium carbonate nanosheets modified pumice and its adsorption of heavy metals - Yong Zhang; Yi-Fan Xiao; Guang-Song Xu; Min-Da Xu; De-Cai Wang; Zhen Jin; Jia-Qi Liu; Li-Li Yang (Environmental Science and Pollution Research, 2023)

In situ microwave-assisted preparation of NS-codoped carbon dots stabilized silver nanoparticles as an off-on fluorescent probe for trace Hg2+ detection - Pengyuan Yin; Tianru Zou; Guixiang Yao; Shaoqing Li; Yanzhi He; Guizhen Li; Da Li; Wei Tan; Min Yang (Chemosphere, 2023)

1,2,4-trihydroxybenzene induces stress granule formation and causes DNA damage in human keratinocytes - Da-Min Jung; Eunhye Kwon; Sunkyung Choi; Kee K. Kim (Toxicology in Vitro, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Intramolecular engineering of defective terminations within triazine-based conjugated polymers for augmented photocatalytic H2 production and Cr(VI) reduction - Zhiquan Jin; Sijia Jin; Shuqi li; Rui Zou; Da Wang; Feilong Dong; Min Liu; Shuang Song; Tao Zeng (Journal of Cleaner Production, 2023)

Robust sugar alcohol with lecithin functionalities for sustainable gelation of edible oils - Eun-Ae Chu; Da-Gyun Park; Eun-Ji Oh; Yeon-Su Lim; Na-Hyeon Kim; Yeong-Min Lee; Kyeong Sik Jin; Jonghoon Choi; Hee-Young Lee (Food Bioscience, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Urban aerosol particulate matter promotes mitochondrial oxidative stress-induced cellular senescence in human retinal pigment epithelial ARPE-19 cells - EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Da Hye Kim; Jung-Hyun Shim; Sung-Kwon Moon; Gi-Young Kim; Jaehun Cheong; Yung Hyun Choi (Environmental Toxicology and Pharmacology, 2023)

Surface solid frustrated Lewis pair constructed on alumina for selective hydrogenation reaction - Zhaowei Tian; Lei Wang; Tianyao Shen; Pan Yin; Weimin Da; Zhitong Qian; Xun Zhao; Guirong Wang; Yusen Yang; Min Wei (Chemical Engineering Journal, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Toxicity and potential underlying mechanism of Karenia selliformis to the fish Oryzias melastigma - Qin-yuan Liu; Zi-min Chen; Da-wei Li; Ai-feng Li; Ying Ji; Hong-ye Li; Wei-dong Yang (Aquatic Toxicology, 2023)

Continuous NO dual-generation by ZnO nanoparticle conjugated with α-lipoic acid for functional biodegradable vascular stent - Seung-Woon Baek; Da-Seul Kim; Jun-Kyu Lee; Jun Hyuk Kim; Semi Lee; Jeong Min Park; So-Yeon Park; Duck Hyun Song; Chun Gwon Park; Dong Keun Han (Chemical Engineering Journal, 2023)

Electron uptake from solid electrodes promotes the more efficient conversion of CO2 to polyhydroxybutyrate by using Rhodobacter sphaeroides - Shuwei Li; Minsoo Kim; Da Seul Kong; Kyoungseon Min; Guangxi Wu; Meiying Cui; Changman Kim; You-Kwan Oh; Soek Kim; Soo Youn Lee; Sung Gyun Kang; Yvonne Nygård; et al. (Chemical Engineering Journal, 2023)

Expression and in vitro function of anti-PD-L1 human antibody expressed in plant - Chae Eun Lee; Jeong Hwan Lee; Hyun Joo Chung; Da Won Lee; Jong Seok Lim; Kibum Kim; Jin Wook Kim; Yong Seong Lee; Kyung Soo Kim; Hyun Jin Min; Kisung Ko; Soon Chul Myung (Plant Biotechnology Reports, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Revealing the influence of microbiota on the flavor of kombucha during natural fermentation process by metagenomic and GC-MS analysis - Lingyun Yao; Jing Zhang; Jun Lu; Da Chen; Shiqing Song; Huatian Wang; Min Sun; Tao Feng (Food Research International, 2023)

Obesity modifies the association of environmental pyrethroid exposure with glucose homeostasis in the US general adults - Ruyi Liang; Xiaobing Feng; Da Shi; Bin Wang; Yongfang Zhang; Wei Liu; Linling Yu; Zi Ye; Min Zhou; Weihong Chen (Environmental Pollution, 2023)

Softened double-layer octopus-like adhesive with high adaptability for enhanced dynamic dry and wet adhesion - Yeon Soo Lee; Gyun Ro Kang; Min-Seok Kim; Da Wan Kim; Changhyun Pang (Chemical Engineering Journal, 2023)

Breast Tissue Reconstruction Using Polycaprolactone Ball Scaffolds in a Partial Mastectomy Pig Model - Kyu-Sik Shim; Da Hye Ryu; Han-Saem Jo; Ki-Bum Kim; Do-Hyun Kim; Yong-Kyu Park; Min Heo; Hee-Eun Cho; Eul-Sik Yoon; Won Jai Lee; Tai Suk Roh; Seung Yong Song; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Aromatic polyketide aspergillones A-D from the endophytic fungus Aspergillus sclerotiorum - Yue Hu; Yi-Lei Zheng; Zhuo-Da Zhou; Min Li; Ming-Ling Wang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2023)

Polybaric fractional crystallization-driven magma differentiation in continental arcs: Insights from the intrusive complex in Langshan arc, southeastern Central Asian Orogenic Belt - Min Liu; Shaocong Lai; Da Zhang; Renzhi Zhu; Jiangfeng Qin; Yu Zhu; Fangyi Zhang; Yongjun Di (Lithos, 2023)

Hongjam prevents hepatic damage against ethanol-induced fatty liver disease in rats - Da-Young Lee; Moon-Young Song; Young-Min Han; Eun-Hee Kim (Journal of Asia-Pacific Entomology, 2023)

Ionic liquid as hydrogen bond acceptor in the extraction of nutritional natural products - Zhixin Xiao; Min Liu; Wentao Bi; David Da Yong Chen (Food Chemistry, 2023)

Evaluation of the 52-week chronic toxicity of a novel phthalate-free plasticizer, Eco-DEHCH (bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate), in Han Wistar rats - Ji-Young Lee; Hyo-Jeong Han; Soo Min Ko; Da Som Jeong; Jiyeon Kang; Dong Hyun Lee; Hwa Jun Cha; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Effects of by-products from producing yacon (Smallanthus sonchifolius) juice as feed additive on growth performance, digestive enzyme activity, antioxidant status, related gene expression, and disease resistance against Streptococcus iniae in juvenile black rockfish (Sebastes schlegelii) - Hwa Yong Oh; Tae Hoon Lee; Chang-Hwan Lee; Da-Yeon Lee; Min-Young Sohn; Ryeong-Won Kwon; Jeong-Gyun Kim; Hee Sung Kim (Aquaculture, 2023)

Analysis of texture properties and water-soluble fraction proteome of sea cucumber body wall with different boiling heating treatment - Min Zhang; Yu-Xin Liu; Zi-Xuan Wu; Guan-Hua Zhao; Liang Song; Peng-Fei Jiang; Man-Man Yu; Da-Yong Zhou (Food Chemistry, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Triterpenoids from the leaves of Abies koreana and their biological activities - Dong Jun Lee; Seong-Min Hong; Da Hye Yoon; Song Lim Ham; Jonghwan Kim; Sun Yeou Kim; Sang Un Choi; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Anti-inflammatory lignan and triterpenoid compounds from the twigs of Ligustrum lucidum - Da Hye Sim; Ngoc Khanh Vu; Duc Dat Le; Ha Ryong Kim; Eun Sook Ma; Byung Sun Min; Mi Hee Woo (Phytochemistry Letters, 2023)

Associations of urinary 1,3-butadiene metabolite with glucose homeostasis, prediabetes, and diabetes in the US general population: Role of alkaline phosphatase - Ruyi Liang; Xiaobing Feng; Da Shi; Linling Yu; Meng Yang; Min Zhou; Yongfang Zhang; Bin Wang; Weihong Chen (Environmental Research, 2023)

Gestational exposure to organophosphate esters and adiposity measures of children up to 6 years: Effect modification by breastfeeding - Yafei Chen; Xiaohua Zhang; Ziliang Wang; Zhengwei Yuan; Min Luan; Wei Yuan; Hong Liang; Hexia Chen; Da Chen; Yan Yang; Maohua Miao (International Journal of Hygiene and Environmental Health, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Genotoxicity assessment of root extracts of Paeonia lactiflora Pall - Su-Min Bak; Seng-Min Back; Da Yeon Kim; Na-Young Jeung; Nan-Young Kim; Jun-Young Yang; Kang-Hyun Han; Yong-Bum Kim; Byung Sun Min; Byoung-Seok Lee; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

0D/3D direct Z-scheme heterojunctions hybridizing by MoS2 quantum dots and honeycomb conjugated triazine polymers (CTPs) for enhanced photocatalytic performance - Shuqi Li; Weishun Lai; Xinming Jiang; Yashuang Wang; Xinyi Cai; Da Wang; Shuang Song; Min Liu; Tao Zeng (Journal of Environmental Sciences, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Prenatal exposure to organophosphate esters is associated with decreased anogenital distance in offspring - Min Luan; Hong Liang; Yafei Chen; Da Chen; Honglei Ji; Hexia Chen; Maohua Miao; Wei Yuan (Science of The Total Environment, 2023)

Studying on effects of boiling on texture, microstructure and physiochemical properties of sea cucumber body wall and its mechanism using second harmonic generation (SHG) microscopy - Min Zhang; Yu-Xin Liu; Guan-Hua Zhao; Liang Song; Zi-Xuan Wu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Plant polysaccharide itself as hydrogen bond donor in a deep eutectic system-based mechanochemical extraction method - Min Liu; Simin Wang; Wentao Bi; David Da Yong Chen (Food Chemistry, 2023)

ε-Poly( -lysine)-based bioreducible nanogels for mitochondria-targeted delivery and release: Hydrophobicity-tuned nucleus-to-mitochondria organelle-targeting switch and slow disulfide cleavage - Hana Cho; Yeon Su Choi; Da Gyeom Choung; Won Gu Choi; Min Seo Lee; Yong-Yeon Cho; Joo Young Lee; Hye Suk Lee; Han Chang Kang (Chemical Engineering Journal, 2023)

Piperock ichnofabrics from western Henan, China: spatial distribution pattern and environmental controls on middle Cambrian carbonates - Bingchen Liu; Da Li; Min Wang; Mingyue Dai; Wenyi He; Jingbo Li; Yong’an Qi (International Journal of Earth Sciences, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Urinary polycyclic aromatic hydrocarbon metabolites and depression: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2016 - Xiaobing Feng; Ruyi Liang; Da Shi; Dongming Wang; Yanjun Guo; Weihong Qiu; Man Cheng; Tao Xu; Chaoqian Dong; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2022)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

TREX1 Deficiency Induces ER Stress-Mediated Neuronal Cell Death by Disrupting Ca2+ Homeostasis - Debasish Halder; Su-Jin Jeon; Ji-Yong Yoon; Jeong-Ju Lee; Soo Young Jun; Min-Hyuk Choi; Bohyeon Jeong; Duk Hyun Sung; Da Yong Lee; Byoung Joon Kim; Nam-Soon Kim (Molecular Neurobiology, 2022)
TREX1 is an exonuclease that degrades extranuclear DNA species in mammalian cells. Herein, we show a novel mechanism by which TREX1 interacts with the BiP/GRP78 and TREX1 deficiency triggers ER stress through the accumulation of single-stranded DNA and activates unfolded protein response (UPR) signaling via the disruption of the TREX1-BiP/GRP78 interaction. In TREX1 knockdown cells, the activation of ER stress signaling disrupted ER Ca 2+ homeostasis via the ERO1α-IP3R1-CaMKII pathway, leading to neuronal cell death. Moreover, TREX1 knockdown dysregulated the Golgi-microtubule network through Golgi fragmentation and decreased Ac-α-tubulin levels, contributing to neuronal injury. These alterations were also observed in neuronal cells harboring a TREX1 mutation (V91M) that has been identified in hereditary spastic paraplegia (HSP) patients in Korea. Notably, this mutation leads to defects in the TREX1-BiP/GRP78 interaction and mislocalization of TREX1 from the ER and possible disruption of the Golgi-microtubule network. In summary, the current study reveals TREX1 as a novel regulator of the BiP/GRP78 interaction and shows that TREX1 deficiency promotes ER stress-mediated neuronal cell death, which indicates that TREX1 may hold promise as a therapeutic target for neurodegenerative diseases such as HSP.

Alternation of stromatolites and vertical burrows controlled by storm processes and sea-level changes in the middle Cambrian carbonates of central China - Bingchen Liu; Mingyue Dai; Yong’an Qi; Xiaofang Sun; Wei Zheng; Min Wang; Zhifeng Xing; Da Li; Yuchao Fan (Journal of Earth System Science, 2022)

Growth and biochemical responses of kale to supplementary irradiation with different peak wavelengths of UV-A light-emitting diodes - Da-Seul Choi; Thi Kim Loan Nguyen; Myung-Min Oh (Horticulture, Environment, and Biotechnology, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Increased serum levels of cadmium are associated with an elevated risk of cardiovascular disease in adults - Siyu Ma; Jie Zhang; Cheng Xu; Min Da; Yang Xu; Yong Chen; Xuming Mo (Environmental Science and Pollution Research, 2022)

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

CRISPR/Cas9-mediated mutation of 5-oxoprolinase gene confers resistance to sulfonamide compounds in Arabidopsis - Ga-Jin Baeg; Seong-Hyeon Kim; Da-Min Choi; Sharanya Tripathi; Yun-Jeong Han; Jeong-Il Kim (Plant Biotechnology Reports, 2021)

Microbiogenic thrombolites from the Cambrian Miaolingian Series of southern North China Craton - Xiaofang Sun; Mingyue Dai; Yong’an Qi; Bingchen Liu; Wei Zheng; Zhifeng Xing; Min Wang; Da Li; Yuchao Fan (Carbonates and Evaporites, 2021)

Changes in the Gene Expression Profiles of the Inferior Colliculus Following Unilateral Cochlear Ablation in Adult Rats - Hog Kwon Kil; Kyung Woon Kim; Da-hye Lee; So Min Lee; Chang Ho Lee; So Young Kim (Biochemical Genetics, 2021)

Generation and Characterization of a Specific Polyclonal Antibody against Arabidopsis thaliana Phytochrome-Interacting Factor 3 - Da-Min Choi; Jae-Yong Cho; Woe-Yeon Kim; Yun-Jeong Han; Jeong-Il Kim (Journal of Plant Biology, 2021)

3,5,4′-Trimethoxy-trans-stilbene loaded microemulsion for cutaneous melanoma therapy by transdermal drug delivery - Jun-Yong Wu; Jia-Xin Cai; Yong-Jiang Li; Xiong-Bin Hu; Xin-Yi Liu; Jie-Min Wang; Tian-Tian Tang; Da-Xiong Xiang (Drug Delivery and Translational Research, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Seasonal analysis of artificial oyster reef ecosystems: implications for sustainable fisheries management - Min Xu; Xin yuan Yang; Xiao jing Song; Kai da Xu; Lin lin Yang (Aquaculture International, 2021)

Hypoxia/reoxygenation-induced upregulation of miRNA-542-5p aggravated cardiomyocyte injury by repressing autophagy - Fei Wang; Xin Min; Shan-you Hu; Da-li You; Ting-ting Jiang; Li Wang; Xiao Wu (Human Cell, 2021)

Dual Oxidase Mutant Retards Mauthner-Cell Axon Regeneration at an Early Stage via Modulating Mitochondrial Dynamics in Zebrafish - Lei-Qing Yang; Min Chen; Da-Long Ren; Bing Hu (Neuroscience Bulletin, 2020)

Genome-wide investigation of a Korean synthetic breed, Woori-Heukdon using the Illumina PorcineSNP60K BeadChip - Yong-Min Kim; Ha-Seung Seong; Jung-Jae Lee; Da-Hye Son; Jin-Su Kim; Soo-Jin Sa; Young-Sin Kim; Tae-Jeong Choi; Kyu-Ho Cho; Joon-Ki Hong; Jung-Woo Choi; Eun-Seok Cho (Genes & Genomics, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Whole-genome resequencing analysis of 20 Micro-pigs - Da-Hye Son; Nam-Hyun Hwang; Won-Hyong Chung; Ha-Seung Seong; Hyungbum Lim; Eun-Seok Cho; Jung-Woo Choi; Kyung-Soo Kang; Yong-Min Kim (Genes & Genomics, 2020)

Effects of high-intensity interval training on adipose tissue lipolysis, inflammation, and metabolomics in aged rats - Lei Sun; Fang-Hui Li; Tao Li; Zhu Min; Luo-Dan Yang; Hao-En Gao; Da-Shuai Wu; Tian Xie (Pflügers Archiv - European Journal of Physiology, 2020)

Short bZIP homologue of sulfur regulator Met4 from Ogataea parapolymorpha does not depend on DNA‐binding cofactors for activating genes in sulfur starvation - Su Jin Yoo; Min Jeong Sohn; Da Min Jeong; Hyun Ah Kang (Environmental Microbiology, 2020)
Summary The acquisition of sulfur from environment and its assimilation is essential for fungal growth and activities. Here, we describe novel features of the regulatory network of sulfur metabolism in Ogataea parapolymorpha , a thermotolerant methylotrophic yeast with high resistance to harsh environmental conditions. A short bZIP protein (OpMet4p) of O. parapolymorpha , displaying the combined structural characteristics of yeast and filamentous fungal Met4 homologues, plays a key role as a master regulator of cell homeostasis during sulfur limitation, but also its function is required for the tolerance of various stresses. Domain swapping analysis, combined with deletion analysis of the regulatory domains and genes encoding OpCbf1p, OpMet28p, and OpMet32p, indicated that OpMet4p does not require the interaction with these DNA‐binding cofactors to induce the expression of sulfur genes, unlike the Saccharomyces cerevisiae Met4p. ChIP analysis confirmed the notion that OpMet4p, which contains a canonical bZIP domain, can bind the target DNA in the absence of cofactors, similar to homologues in other filamentous fungi. Collectively, the identified unique features of the O. parapolymorpha regulatory network, as the first report on the sulfur regulation by a short yeast Met4 homologue, provide insights into conservation and divergence of the sulfur regulatory networks among diverse ascomycetous fungi.

Middle Permian high Sr/Y monzogranites in central Inner Mongolia: reworking of the juvenile lower crust of Bainaimiao arc belt during slab break-off of the Palaeo-Asian oceanic lithosphere - Min Liu; Shaocong Lai; Da Zhang; Renzhi Zhu; Jiangfeng Qin; Guangqiang Xiong (International Geology Review, 2019)

Intracutaneous Delivery of Gelatins Reduces Fat Accumulation in Subcutaneous Adipose Tissue - Sung-Min An; Min Jae Kim; Keum-Yong Seong; Jea Sic Jeong; Hyeon-Gu Kang; So Young Kim; Da Som Kim; Da Hee Kang; Seung Yun Yang; Beum-Soo An (Toxicological Research, 2019)

Early-Middle Triassic Intrusions in Western Inner Mongolia, China: Implications for the Final Orogenic Evolution in Southwestern Xing-Meng Orogenic Belt - Min Liu; Shaocong Lai; Da Zhang; Renzhi Zhu; Jiangfeng Qin; Yongjun Di (Journal of Earth Science, 2019)

Arabidopsis GIGANTEA negatively regulates chloroplast biogenesis and resistance to herbicide butafenacil - Joon-Yung Cha; Da-Yeon Lee; Imdad Ali; Song Yi Jeong; Bobae Shin; Hyunjung Ji; Jung Sun Kim; Min-Gab Kim; Woe-Yeon Kim (Plant Cell Reports, 2019)

In vitro tissue culture of apple and other Malus species: recent advances and applications - Jaime A. Teixeira da Silva; Andrea Gulyás; Katalin Magyar-Tábori; Min-Rui Wang; Qiao-Chun Wang; Judit Dobránszki (Planta, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Loss of Arabidopsis Halotolerance 2-like (AHL), a 3′-phosphoadenosine-5′-phosphate phosphatase, suppresses insensitive response of Arabidopsis thaliana ring zinc finger 1 (atrzf1) mutant to abiotic stress - Da-Jeong Shin; Ji-Hee Min; Tinh Van Nguyen; Young-Min Kim; Cheol Soo Kim (Plant Molecular Biology, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Desorption of Hydrophobic Organic Chemicals from Fragment-Type Microplastics - Hwang Lee; Da-Eun Byun; Ju Min Kim; Jung-Hwan Kwon (Ocean Science Journal, 2018)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Characterization of high temperature-tolerant strains of Pyropia yezoensis - Yoon Ju Shin; Sung Ran Min; Da Yeon Kang; Jong-Min Lim; Eun-Jeong Park; Mi Sook Hwang; Dong-Woog Choi; Joon-Woo Ahn; Youn-Il Park; Won-Joong Jeong (Plant Biotechnology Reports, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Improvement of indoor air quality in pet shop using gaseous chlorine dioxide - Ming-Chun Lu; Da-Ji Huang; Ching-Shan Hsu; Chih-Kuo Liang; Geng-Min Chen (Environmental Monitoring and Assessment, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Versicolorin A is a potential indicator of aflatoxin contamination in the granary-stored corn - Shu-Yao Zhang; Hao Wang; Min Yang; Dong-Sheng Yao; Chun-Fang Xie; Da-Ling Liu (Food Additives & Contaminants: Part A, 2018)

Cryobiotechnology of apple (Malus spp.): development, progress and future prospects - Min-Rui Wang; Long Chen; Jaime A. Teixeira da Silva; Gayle M. Volk; Qiao-Chun Wang (Plant Cell Reports, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Mental Stress from Animal Experiments: a Survey with Korean Researchers - Minji Kang; AhRam Han; Da-eun Kim; Troy Seidle; Kyung-Min Lim; SeungJin Bae (Toxicological Research, 2018)

Evaluation of the effects of the combination of autologous mesenchymal stem cells and platelet-rich plasma on structural bone allograft healing - Chang-Goo Park; Min Wook Joo; Jinyoung Jeong; Yong-Koo Kang; Da-Reum Lee (Cell and Tissue Banking, 2017)

Ocular safety of Intravitreal Clindamycin Hydrochloride Released by PLGA Implants - Gabriella M. Fernandes-Cunha; Silvia Ligório Fialho; Gisele Rodrigues da Silva; Armando Silva-Cunha; Min Zhao; Francine Behar-Cohen (Pharmaceutical Research, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Lentiviral Vector-Mediated p27kip1 Expression Facilitates Recovery After Spinal Cord Injury - Min-hao Chen; Yong-hua Liu; Hua Xu; Da-wei Xu; Cheng-niu Wang; Yi- Wang; Cheng-wei Duan; Ying Zhou; Peng Kan; Ai-guo Shen; You-hua Wang (Molecular Neurobiology, 2016)

Stochastic finite modeling of ground motion for March 5, 2012, Mw 4.6 earthquake and scenario greater magnitude earthquake in the proximity of Delhi - Himanshu Mittal; Yih-Min Wu; Da-Yi Chen; Wei-An Chao (Natural Hazards, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Sesquiterpene lactone parthenolide attenuates production of inflammatory mediators by suppressing the Toll-like receptor-4-mediated activation of the Akt, mTOR, and NF-κB pathways - Yoon Jeong Nam; Da Hee Lee; Min Sung Lee; Chung Soo Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Benzo(a)pyrene represses melanogenesis in B16F10 mouse melanoma cells - Da Hye Joo; Hwa Jun Cha; Karam Kim; Minhee Jung; Jung Min Ko; In Sook An; Sung Nae Lee; Hyun Hee Jang; Seunghee Bae; Nam Kyung Roh; Kyu Joong Ahn; Sungkwan An (Molecular & Cellular Toxicology, 2015)

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Simultaneous determination of seven active ingredients in rat plasma by UPLC-MS/MS and application in pharmacokinetic studies after oral administration of scutellaria-coptis herb couple - Le-yue Du; Jian-ming Guo; Da-wei Qian; Er-xin Shang; Shu Jiang; Pei Liu; Shu-lan Su; Fang Zhang; Jin-ao Duan; Jun Xu; Min Zhao (Medicinal Chemistry Research, 2015)

Effects of biochar amendment on rice growth and nitrogen retention in a waterlogged paddy field - Da Dong; Qibo Feng; Kim McGrouther; Min Yang; Hailong Wang; Weixiang Wu (Journal of Soils and Sediments, 2015)

Rotundarpene prevents TRAIL-induced apoptosis in human keratinocytes by suppressing the caspase-8- and Bid-pathways and the mitochondrial pathway - Da Hee Lee; Yoon Jeong Nam; Yun Jeong Kim; Min Won Lee; Chung Soo Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Simvastatin Pretreatment Protects Cerebrum from Neuronal Injury by Decreasing the Expressions of Phosphor-CaMK II and AQP4 in Ischemic Stroke Rats - Min-xia Zhu; Chao Lu; Chun-mei Xia; Zhong-wei Qiao; Da-nian Zhu (Journal of Molecular Neuroscience, 2014)

Enhancing Nutritional Quality of Silage by Fermentation with Lactobacillus plantarum - Mariadhas Valan Arasu; Min-Woong Jung; Da Hye Kim; Soundharrajan Ilavenil; Mariamichael Jane; Hyung Su Park; Naif Abdullah Al-Dhabi; Byong Tae Jeon; Ki Choon Choi (Indian Journal of Microbiology, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Ichnofabrics and their environmental interpretation from the fluvial deposits of the Middle Triassic Youfangzhuang Formation in Western Henan, Central China - Min Wang; Yongan Qi; Da Li; Mingyue Dai; Yuguang Chang (Journal of Earth Science, 2014)

Anterolateral minithoracotomy versus median sternotomy for mitral valve disease: a meta-analysis - Chao Ding; Da-ming Jiang; Kai-yu Tao; Qun-jun Duan; Jie Li; Min-jian Kong; Zhong-hua Shen; Ai-qiang Dong (Journal of Zhejiang University-SCIENCE B, 2014)

Interactions between soybean ABA receptors and type 2C protein phosphatases - Ge Bai; Da-Hai Yang; Yang Zhao; Si Ha; Fen Yang; Jun Ma; Xiao-Shu Gao; Zhi-Min Wang; Jian-Kang Zhu (Plant Molecular Biology, 2013)

Climate change in the 21st century simulated by HadGEM2-AO under representative concentration pathways - Hee-Jeong Baek; Johan Lee; Hyo-Shin Lee; Yu-Kyung Hyun; ChunHo Cho; Won-Tae Kwon; Charline Marzin; Sun-Yeong Gan; Min-Ji Kim; Da-Hee Choi; Jonghwa Lee; Jaeho Lee; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Da Xiong Han; Hai Yan Wang; Hong Wei Yue; Su Min Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Responses of methane emissions and rice yield to applications of biochar and straw in a paddy field - Da Dong; Min Yang; Cheng Wang; Hailong Wang; Yi Li; Jiafa Luo; Weixiang Wu (Journal of Soils and Sediments, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Three new secolignan glycosides from Urtica fissa E. Pritz - Bao-min Feng; Hai-hong Qin; Hui-guo Wang; Li-ying Shi; Da-yong Yu; Bao-quan Ji; Qi Zhao; Yong-qi Wang (Journal of Natural Medicines, 2012)

Recognition of early Carboniferous alkaline granite in the southern Altai orogen: post-orogenic processes constrained by U–Pb zircon ages, Nd isotopes, and geochemical data - Ying Tong; Tao Wang; Wolfgang Siebel; Da-Wei Hong; Min Sun (International Journal of Earth Sciences, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Secretory expression and characterization of a soluble laccase from the Ganoderma lucidum strain 7071-9 in Pichia pastoris - Jing Sun; Ri-He Peng; Ai-Sheng Xiong; Yongsheng Tian; Wei Zhao; Hu Xu; Da-Tong Liu; Jian-Min Chen; Quan-Hong Yao (Molecular Biology Reports, 2012)

Calcite cements in burrows and their influence on reservoir property of the Donghe sandstone, Tarim Basin, China - Yongan Qi; Min Wang; Wei Zheng; Da Li (Journal of Earth Science, 2012)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Metaproteomic characterization of dissolved organic matter in the water column of the South China Sea - Da-Zhi Wang; Hong-Po Dong; Zhang-Xian Xie; Min-Han Dai; Hua-Sheng Hong (Limnology and Oceanography, 2011)
We characterized dissolved organic matter (DOM;

Analysis of the fungi community in multiple- and single-grains Zaopei from a Luzhou-flavor liquor distillery in western China - Si Shi; Lei Zhang; Zheng-yun Wu; Wen-xue Zhang; Yu Deng; Fang-da Zhong; Jia-min Li (World Journal of Microbiology and Biotechnology, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Expression and identification of a thermostable malate dehydrogenase from multicellular prokaryote Streptomyces avermitilis MA-4680 - Zong-Da Wang; Bao-Juan Wang; Ya-Dong Ge; Wei Pan; Jie Wang; Lei Xu; Ai-Min Liu; Guo-Ping Zhu (Molecular Biology Reports, 2011)

Seasonal and interannual variations in carbon dioxide exchange over a cropland in the North China Plain - HUI‐MIN LEI; DA‐WEN YANG (Global Change Biology, 2010)
In China, croplands account for a relatively large form of vegetation cover. Quantifying carbon dioxide exchange and understanding the environmental controls on carbon fluxes over croplands are critical in understanding regional carbon budgets and ecosystem behaviors. In this study, the net ecosystem exchange (NEE) at a winter wheat/summer maize rotation cropping site, representative of the main cropping system in the North China Plain, was continuously measured using the eddy covariance technique from 2005 to 2009. In order to interpret the abiotic factors regulating NEE, NEE was partitioned into gross primary production (GPP) and ecosystem respiration ( R eco ). Daytime R eco was extrapolated from the relationship between nighttime NEE and soil temperature under high turbulent conditions. GPP was then estimated by subtracting daytime NEE from the daytime estimates of R eco . Results show that the seasonal patterns of the temperature responses of R eco and light‐response parameters are closely related to the crop phenology. Daily R eco was highly dependent on both daily GPP and air temperature. Interannual variability showed that GPP and R eco were mainly controlled by temperature. Water availability also exerted a limit on R eco . The annual NEE was −585 and −533 g C m −2 for two seasons of 2006–2007 and 2007–2008, respectively, and the wheat field absorbed more carbon than the maize field. Thus, we concluded that this cropland was a strong carbon sink. However, when the grain harvest was taken into account, the wheat field was diminished into a weak carbon sink, whereas the maize field was converted into a weak carbon source. The observations showed that severe drought occurring during winter did not reduce wheat yield (or integrated NEE) when sufficient irrigation was carried out during spring.

Tissue-specific distribution of uncoupling proteins in normal rats and rats with high-fat-diet-induced obesity - Chun-Mei Zhang; Ying Gu; Da-ni Qing; Jin-gai Zhu; Chun Zhu; Min Zhang; Xi-Rong Guo (Molecular Biology Reports, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Periodic ichnofabric couplets indicative of paleoclimate variations in the Upper Cambrian Gushan Formation, North China - Yongan Qi; Min Wang; Da Li; Yuyang Yuan (Journal of Earth Science, 2010)

Genes required for the functions of olfactory AWA neuron regulate the longevity of Caenorhabditis elegans in an insulin/IGF signaling-dependent fashion - Lu-Lu Shen; Min Du; Xing-Feng Lin; Ting Cai; Da-Yong Wang (Neuroscience Bulletin, 2010)

Lactational coumestrol exposure increases ovarian apoptosis in adult rats - Hyun-Ju Moon; Ji Hyun Seok; Soon Sun Kim; Gyu Seek Rhee; Rhee Da Lee; Jun Young Yang; Soo Yeong Chae; Seung Hee Kim; Ji Young Kim; Jin-Yong Chung; Jong-Min Kim; Soo Youn Chung (Archives of Toxicology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Genotypic and environmental variation in cadmium, chromium, arsenic, nickel, and lead concentrations in rice grains - Wang-da Cheng; Guo-ping Zhang; Hai-gen Yao; Wei Wu; Min Xu (Journal of Zhejiang University-SCIENCE B, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

Phylogenetic Analysis of Canine Parvovirus VP2 Gene in Taiwan - Hsien-Chi Wang; Wei-Da Chen; Shiun-Long Lin; Jacky Peng-Wen Chan; Min-Liang Wong (Virus Genes, 2005)

Isolation and characterization of a novel strain of Natrinema containing a bop gene - Xue-wei Xu; Min Wu; Wei-da Huang (Journal of Zhejiang University-SCIENCE B, 2005)

Gold Immunolocalization of Rubisco and Rubisco Activase in Pyrenoid of Chlamydomonas reinhardtii - Pei-Min He; Da-Bing Zhang; Geng-Yun Chen; Qi-Gen Liu; Wei-Ning Wu (Algae, 2003)

DELIVERY AND STORAGE OF SINGLE EMBRYOS, SPERM, OR CELLS IN MICROGLASS CAPILLARIES - Min-Kang Wang; Ji-Long Liu; Li Lian; Da-Yuan Chen (In Vitro Cellular & Developmental Biology - Animal, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)